SERVANT LEADERSHIP AND SERVICE QUALITY IN CONTEMPORARY ORGANIZATIONS: A SYSTEMATIC LITERATURE REVIEW - Mohd Zulkeflee Bin Abd Razak; Lili Fadli Muhamad; Norziah Bin Othman (Program Studi Pengembangan Masyarakat Islam STID Mohammad Natsir, 2026)
In service-driven economies, leadership is widely recognised as a critical determinant of service quality and long-term organizational sustainability. Among contemporary leadership approaches, servant leadership has attracted growing scholarly interest due to its ethical grounding, relational focus, and emphasis on employee development. Despite this attention, empirical evidence linking servant leadership to service quality remains fragmented across sectors, research designs, and conceptual perspectives. To address this limitation, the present study conducts a systematic literature review synthesising recent research on the relationship between servant leadership and service quality, as well as related service outcomes. Drawing on 20 peer-reviewed journal articles published between 2021 and 2025, the review systematically examines dominant thematic patterns, underlying mechanisms, and contextual conditions shaping leadership effectiveness. The findings indicate that servant leadership is consistently associated with enhanced service quality, service performance, and service-oriented behaviours. However, these effects are predominantly indirect, operating through psychological and organizational mechanisms such as psychological empowerment, psychological safety, work engagement, felt obligation, and internal service quality. The review further highlights the multi-level nature of servant leadership, demonstrating its influence on both individual employee behaviour and broader organizational service systems. Importantly, cultural orientation, human resource systems, and sustainability priorities emerge as key boundary conditions shaping leadership outcomes. By consolidating dispersed evidence, this review advances theoretical understanding of the servant leadership–service quality nexus and offers practical insights for fostering sustainable service excellence.